2019
DOI: 10.3389/fnhum.2019.00419
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Information Flow in Resting-State in Adolescents With Sports Related Concussion

Abstract: Children and youths are at a greater risk of concussions than adults, and once injured, take longer to recover. A key feature of concussion is an increase in functional connectivity, yet it remains unclear how changes in functional connectivity relate to the patterns of information flow within resting state networks following concussion and how these relate to brain function. We applied a data-driven measure of directed effective brain connectivity to compare the patterns of information flow in healthy adolesc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 60 publications
0
43
2
Order By: Relevance
“…We propose that widespread injury can reduce rule-based skilled performance through a failure to communicate between brain networks. Cognitive brain network alterations have been observed following concussion (13)(14)(15)(16)(17). To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration).…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…We propose that widespread injury can reduce rule-based skilled performance through a failure to communicate between brain networks. Cognitive brain network alterations have been observed following concussion (13)(14)(15)(16)(17). To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration).…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…However, prior to extracting the features, we had filtered the data [82][83][84] to remove signal drift, an approach that is commonly adopted to mitigate weak non-stationary behaviour. This works well enough when one is interested in population-level differences between concussed and healthy groups [24,28,47,48]. However, the distribution functions of features for the healthy and concussed individuals overlap, which hampers attempts to use the features to assess individual subjects.…”
Section: Network Architecturementioning
confidence: 99%
“…Symptoms, however, do not appear to be directly correlated to the patho-physiological mechanisms responsible for the cognitive, emotional and behavioral deficits [13,14] and several studies [14][15][16][17][18][19][20][21][22][23] have shown that structural and functional abnormalities in the brain persist even after symptom resolution, especially in pediatric patients. Manning et al [20] and Hristopulos et al [24] hypothesize that the increased vulnerability of children and youths to brain injury, as well as their longer recovery time, are consequences of the effects of concussion being overlaid on brains whose structural and functional organization are undergoing dynamic changes due to development. Moreover, recovering individuals are also at a higher risk of sustaining additional concussions, which can lead to neuro-psychiatric and neuro-degenerative disorders [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations